2021
DOI: 10.1002/jsde.12530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sulfate‐Reducing Bacteria by Para‐amino‐N‐((1‐Alkylpyridin‐1‐Ium Bromide)‐4‐Yl) Benzamide Surfactants and Surfactant‐Coated Silver Nanoparticles

Abstract: In the present work, we report the antibacterial activity of silver nanoparticles (AgNP) coated with the surfactants para‐amino‐N‐((1‐decylpyridin‐1‐ium bromide)‐4‐yl) benzamide and para‐amino‐N‐((1‐dodecylpyridin‐1‐ium bromide)‐4‐yl) benzamide (P10 and P12, respectively). P10 and P12‐coated AgNP were stable, as confirmed by ultraviolet–visible spectrophotometry, transmission electron microscopy, and other surface activity parameters. Both P10 and P12 and the coated AgNP formulations were investigated for thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Therefore, the presence of alkyl chains (hexadecyl) in compound P16 enhanced the stability of the AgNPs. It was concluded that the alkyl chain length provided a physical barrier, preventing aggregation between the surfaces of AgNPs during collisions, in addition to the effect of P16 molecules on the charge of AgNPs; that is, the P16 reduced the surface charge of the AgNPs [ 40 ]. These factors led to an overall reduction in the aggregation of AgNPs, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the presence of alkyl chains (hexadecyl) in compound P16 enhanced the stability of the AgNPs. It was concluded that the alkyl chain length provided a physical barrier, preventing aggregation between the surfaces of AgNPs during collisions, in addition to the effect of P16 molecules on the charge of AgNPs; that is, the P16 reduced the surface charge of the AgNPs [ 40 ]. These factors led to an overall reduction in the aggregation of AgNPs, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the SEM image in Figure 3 gives an indication about the aggregation of the Ag-nanoparticles which were produced as a result of the surface plasmon charges on the silver nanoparticles. It is known that metal particles in colloidal solution usually have a negative charge due to adsorbed anions; this leads to more aggregation of such particles in solution, as shown in Figure 3 [ 40 ]. Further investigation of the nanostructure of the P16 capped AgNPs ( P16-AgNPs ) is summarized in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations